Concepts Conveying the Meaning of “Freedom” in the old Georgian Language - Robakidze, Merab (Actual Problems of Kartvelology, 2025)
Disclosing ancient (primary) word meanings by linguists is of great importance for revealing early representations of these or those people on an objective reality. Freedom _ the motivating force of mankind. Without it this or that nation cannot exist and develop, cannot create national culture, nor protect the advantage. Free can be both the individual person and society. "Freedom" - the most ancient concepts of the Georgian language regularly met both in the Bible and of many monuments of the ancient Georgian literature; it is widely used in modern Georgian language; the concept of "freedom" has some synonyms. Along this, the concepts which are of interest for deep studying of a phenomenon of "freedom" are allocated. "Freedom" represents concept of the proof maintenance. Its definition is unequivocal in the historical and modern plan. The concept of "freedom" ("clearing") of ancient Georgian language is presented by group of keywords which recreate difficult step character of ideological loading of "clearing". Each of them has special value in disclosing full process of "clearing" the meaning. Such words are "tavis-upleba", "sky", "nebiskopa", "guls-modgineba", "rescue" ("outcome"). The free will of the person represents inner and innate phenomenon, divine gift. The person is free in the choice, that he uses the will to make a free choice, plan a way of the action. The further success in business depends on the correctness of a free choice. Thus, it is necessary to remark that a personal will needs to be realised in business, whereas "freedom" will not be reached. In the Georgian concept "tavis-upleba" the idea of ability of free choice is displayed, "guls-modgineia" means "will", "nebis-kopa" comprises the sense of "will realizations". And concepts such as "khsna"(rescue) and "ganrineba"(liberation) convey the meaning of pushing away and separating from oppressing, connecting and bad force. Our research shows that the term "tavisupleba" (freedom) in old Georgian language and shows original understanding of the essence of a problem.